2015
DOI: 10.1063/1.4921789
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the formation of CoFe2C phase with colossal magnetocrystalline-anisotropy

Abstract: Articles you may be interested inEnhanced magnetic behavior, exchange bias effect, and dielectric property of BiFeO3 incorporated in (BiFeO3)0.50 (Co0.4Zn0.4Cu0.2 Fe2O4)0.5 nanocomposite AIP Advances 4, 037112 (2014); 10.1063/1.4869077Facile synthesis of single-phase spherical α″-Fe16N2/Al2O3 core-shell nanoparticles via a gas-phase method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Co 2 C is orthorhombic, and has been produced in the form of coercive nanoparticles, with a relatively small magnetization [44]. The magnetization of CoFe 2 C nanoparticles is slightly higher, but they exhibits even less coercivity, despite a questionable claim of exceptional magnetocrystalline anisotropy in this compound [45].…”
Section: New Materialsmentioning
confidence: 99%
“…Co 2 C is orthorhombic, and has been produced in the form of coercive nanoparticles, with a relatively small magnetization [44]. The magnetization of CoFe 2 C nanoparticles is slightly higher, but they exhibits even less coercivity, despite a questionable claim of exceptional magnetocrystalline anisotropy in this compound [45].…”
Section: New Materialsmentioning
confidence: 99%
“…In this study, using density-functional theory (DFT) calculations, we consider carbon (C) as an alternative dopant to B in fabricating a CoFe/MgO MTJ, due to the comparable atomic radii of B and C atoms. CoFeC alloys can exhibit colossal magnetocrystalline anisotropy [26] and retain a good epitaxy with the MgO layer [27]. However, the behavior of the C dopant in the annealing process of CoFe/MgO/CoFe MTJ fabrication and its impact on device TMR are less known.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several Fe-based RE-free compounds such as Fe-Co-X (X being B, C or N) [2][3][4][5][6][7], Fe(Co)Pt [8], and Fe 2 P [9] have been studied intensively as potential permanent magnet materials. These studies have demonstrated that the MAE of Fe can be improved substantially by allowing with other non-magnetic elements.…”
Section: Introductionmentioning
confidence: 99%